Congenital lymphedema a literature review - Annoni, Gustavo Matge; Xavier, Henrique Souza; de Mello, Pedro Henrique Jarré; Júnior, Márcio da Silva Lara; Ledur, Lucas Ortiz; Artifon, Otávio Augusto Nesi; Marques, Higor Goulart; Luz, Karine; Locatelli, Claudriana (Seven Editora, 2024)
Congenital lymphedema is a rare and chronic medical condition characterized by abnormal development or function of the lymphatic system, resulting in localized edema and enlargement of tissues, usually in the extremities. This condition is present from birth or becomes evident during childhood. It can be classified into primary and secondary types, with primary congenital lymphedema being linked to genetic mutations affecting the lymphatic vessels and secondary congenital lymphedema due to other congenital conditions or developmental problems. The diagnosis of congenital lymphedema is typically based on clinical examination and may be supported by imaging studies such as lymphoscintigraphy. Management and treatment aim to relieve symptoms and improve patients’ quality of life. Therapeutic approaches often include manual lymphatic drainage, compression therapy, and skin care practices to reduce swelling and prevent complications such as cellulite. Genetic counseling may be relevant for cases of primary congenital lymphedema, while treatment of secondary congenital lymphedema may address the underlying causes. In summary, congenital lymphedema is a genetic condition that requires early diagnosis, multidisciplinary treatment, and a thorough approach to lessen its impact on affected individuals. Understanding its genetic and secondary causes is essential for providing appropriate care and support to people living with this condition. DOI:https://doi.org/10.56238/innovhealthknow-040